Turkish Early Childhood Educators on Parental Involvement - Sevcan Hakyemez (Symposium Journals, 2022)
Research conducted over recent decades show that parental involvement plays a significant role in children's academic achievement as well as their cognitive, social and emotional development. For effective parental involvement, understanding the conceptualisation of early childhood educators should be significant. This research investigated the views of Turkish early childhood educators on parental involvement and attitudes towards its types. Furthermore, it aims to find the reasons behind inefficient usage. A total of 113 educators provided a representative sample from Ankara. The results showed that Turkish early childhood educators have positive attitudes towards parental involvement and its types. In additon, the most popular type of parental involvement is home support. According to the results, the main reason for inefficient parental involvement is the unwillingness of parents to participate.